Questions, Questions: Has Weber Had an Impact on Unions’ Representational Responsibilities in Workplace Human Rights Disputes? - Mummé, Claire (One law for all? Weber v Ontario Hydro and Canadian labour law: essays in memory of Bernie Adell, 2017)
This essay attempts to put forward a research agenda for properly evaluating the changing nature of unions’ human rights representational obligations since Weber. I begin by investigating two legal questions: first, whether unions are held to a more stringent duty of fair representation (DFR) standard in regards to members’ discrimination grievances than prior to Weber and Parry Sound, and second, whether there has been a broadening of the concept of union discrimination under human rights codes, such that unions may be held liable for failing to bring forward discrimination grievances. With the legal picture in place, I then set out a series of empirical questions that need further research to properly assess whether, and to what extent, Weber and Parry Sound have altered unions’ human rights obligations in the administration of collective agreements, and more generally, their approaches to dealing with human rights issues in the workplace. The essay intentionally raises more questions than it answers, with the objective of provoking further research on important issues regarding labour law in action.
Keywords: Claire Mummé